2013
DOI: 10.1128/cvi.00607-13
|View full text |Cite
|
Sign up to set email alerts
|

Blood Collection Tubes Influence Serum Ficolin-1 and Ficolin-2 Levels

Abstract: The ficolins are members of a recently discovered family of host innate opsonins that can activate the lectin pathway of complement. The ficolins bind many ligands, although they are typically described as binding acetylated sugars. Ficolin-1 (M-ficolin) and ficolin-2 (L-ficolin) are known to bind Streptococcus pneumoniae serotypes 19C and 11A, respectively. While studying the binding of ficolins to pneumococci, we found variations in ficolin-2 binding among serum samples collected in different types of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
1
31
2
Order By: Relevance
“…Though the inhibitor present in plastic blood collection tubes affects detection of ficolin-2 by ELISA and flow cytometry, sequestered ficolin-2 is still visible by Western blotting (15). Therefore, we assayed NHS and all of the depleted sera for ficolin-2 by Western blotting to determine if the absence of ficolin-2 in the complement component-depleted sera may be due to the type of tube used during blood collection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the inhibitor present in plastic blood collection tubes affects detection of ficolin-2 by ELISA and flow cytometry, sequestered ficolin-2 is still visible by Western blotting (15). Therefore, we assayed NHS and all of the depleted sera for ficolin-2 by Western blotting to determine if the absence of ficolin-2 in the complement component-depleted sera may be due to the type of tube used during blood collection.…”
Section: Resultsmentioning
confidence: 99%
“…Complement component-depleted sera are codepleted of ficolin-2. We previously found that plastic blood collection tubes contain a ficolin-2-specific inhibitor that sequesters ficolin-2, effectively inhibiting ficolin-2 binding to pneumococci (15). To investigate if C1q-depleted sera inhibited ficolin-2 binding, we mixed rFicolin-2 supernatant with C1q-depleted sera and studied ficolin-2 binding to serotype 11A bacteria using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values for young, healthy controls were previously reported (Brady et al, 2014c). In mixing experiments, each serum sample was tested alone at 20-fold dilution (15 µl serum + 285 µl kit dilution buffer).…”
Section: Methodsmentioning
confidence: 99%
“…Besides anticoagulants, the blood collection tube contains multiple components such as clotting activator, silicones, a silica clot activator, and polymeric surfactants (34,35), all of which may affect the assays. Appropriate blood collection is crucial for accurate immunomonitoring of human clinical samples.…”
Section: Discussionmentioning
confidence: 99%